2012
DOI: 10.1007/s10140-012-1027-2
|View full text |Cite
|
Sign up to set email alerts
|

Early assessment of the efficacy of digital infrared thermal imaging in pediatric extremity trauma

Abstract: Young children or those with intellectual disability with trauma to an extremity often undergo radiographs of the whole limb. The objective of the study was to assess the efficacy of digital infrared thermal images (DITI) in pediatric extremity trauma. We hypothesized fractures to be associated with local hyperthermia, detectable with DITI, which could direct focused radiographs. In this exploratory study, patients seen over a 2-month period in a pediatric emergency department for limb trauma were included if … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 32 publications
1
27
0
Order By: Relevance
“…Sanchis-Sánchez et al explored the use of IRT in ruling out fractures in paediatric trauma patients, reporting a sensitivity of 0.91 and a specificity of 0.88. 18 Similarly, Silva et al 19 examined the use of IRT in locating areas of trauma in 51 patients, finding that the technology matched the site of pain in 73% of locations, as well as 7 out of 11 fracture sites. Ćurković et al used IRT in 19 children with forearm fracture: the average temperature of the injured side was 1.17°C higher than that of the healthy side after 1 week and 0.84°C higher after 2 weeks; however, Ćurković et al were unable to produce statistically significant results due to the small sample size.…”
Section: Irt In Childrenmentioning
confidence: 99%
“…Sanchis-Sánchez et al explored the use of IRT in ruling out fractures in paediatric trauma patients, reporting a sensitivity of 0.91 and a specificity of 0.88. 18 Similarly, Silva et al 19 examined the use of IRT in locating areas of trauma in 51 patients, finding that the technology matched the site of pain in 73% of locations, as well as 7 out of 11 fracture sites. Ćurković et al used IRT in 19 children with forearm fracture: the average temperature of the injured side was 1.17°C higher than that of the healthy side after 1 week and 0.84°C higher after 2 weeks; however, Ćurković et al were unable to produce statistically significant results due to the small sample size.…”
Section: Irt In Childrenmentioning
confidence: 99%
“…Infrared imaging revealed body temperatures in peripheral and central areas of the body simultaneously, allowing us to visualize a temperature differential between these areas. Researchers have successfully used infrared thermal imaging to locate areas of peripheral body temperature differentials to diagnose limb trauma with altered perfusion in pediatric patients (Silva et al., ). This exploratory technology may be useful in determining why infants have periods with increased peripheral temperature while keeping their central temperature cold.…”
Section: Resultsmentioning
confidence: 99%
“…It is also necessary to identify relevant temperature values that correlate to the healing process observed in x-rays (Ćurković et al, 2015;Haluzan et al, 2015). Aside from better thermal analysis, preparation of alternative methods to make IRT practical in a busy emergency department constitutes a future challenge (Silva et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The comparison of radiographic scans and thermograms from both healthy patients and patients with fractured forearm, throughout a month period, allowed the identification of noticeable skin temperature differences between healthy and injured patients. In another pediatric study, Silva et al (2012), aiming to attest the efficacy of early assessment of extremity trauma, reported a successful matching of 73% of the upper limbs pain sites and 63% of the fracture regions. Additionally, Haluzan et al (2015) found preliminary findings concerning temperature differences between healthy participants and patients with forearm distal radius fracture.…”
Section: Health Recovery Monitoringmentioning
confidence: 99%